Interaction and Negotiation between Islamic Law and Customary Law in the Distribution of Inheritance for Women (Study in Sukarame Village, Pakpak Bharat) - Barasa, Chairani; Armia, Muhammad Siddiq; M. Yunus, Saifullah (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2026)
The distribution of inheritance for women in customary communities continues to exhibit tension between Islamic legal norms and customary law practices within societies that adhere to a patrilineal kinship system. However, studies specifically examining the interaction of these two legal systems within a local context, particularly among the Pakpak community, remain limited. Therefore, this research aims to analyze the interaction between Islamic law and customary law regarding the distribution of inheritance for women in Sukarame Village, Kerajaan District, Pakpak Bharat Regency. This study employs a qualitative method with an empirical-juridical approach and a case study design. Data were collected through in-depth interviews with customary leaders, religious figures, and community members, supplemented by field observations. The research findings indicate that inheritance distribution practices remain dominated by Pakpak customary law, which is rooted in a patrilineal system where men serve as the primary beneficiaries of the inheritance. Women generally do not receive a formal share, but rather only receive voluntary gifts. Nevertheless, the influence of Islamic law has begun to emerge in several families, although its application is not yet entirely consistent with the principles of faraid. This research concludes that the interaction between Islamic law and customary law is unbalanced, characterized by the dominance of customary law in practice. The scientific contribution of this study lies in reinforcing the study of legal pluralism by demonstrating the gap between Islamic legal norms and customary practices at the local level. Practically, this research emphasizes the importance of enhancing the community's understanding of Islamic inheritance law to strengthen the protection of women's rights.